Programmable liquid crystal elastomer microactuators prepared via thiol–ene dispersion polymerization. Issue 21 (26th May 2020) - Liu, Xiaohong; Pan, Xinglong; Debije, Michael G.; Heuts, Johan P. A.; Mulder, Dirk J.; Schenning, Albert P. H. J.
Abstract : Programmable, narrowly dispersed, 10 micron-sized, liquid crystalline elastomer actuators were first prepared via thiol–ene dispersion polymerization and then deformed in a PVA film, followed by photopolymerization of the residual acrylate groups. Abstract : Narrowly dispersed, 10 micron-sized, liquid crystalline elastomer polymer actuators were first prepared via thiol–ene dispersion polymerization and then embedded and stretched in a polyvinyl alcohol film, followed by photopolymerization of the residual acrylate groups. Prolate micro spheroids in which the mesogens are aligned parallel to the long axis were obtained and showed reversible thermally driven actuation owing to nematic to isotropic transition of the liquid crystal molecules. The particles were also compressed to form disk-shaped oblate microactuators in which the mesogens are aligned perpendicular to the short axis, demonstrating that the reported method is a versatile method to fabricate liquid crystal elastomer microactuators with programmable properties.